Quality of life of 1276 elderly patients with prostate cancer, starting treatment with a gonadotropin-releasing hormone agonist: results of a French observational study. (June 2014) - Lebret, Thierry; Culine, Stéphane; Davin, Jean-Louis; Hennequin, Christophe; Mignard, Jean-Pierre; Moreau, Jean-Luc; Rossi, Dominique; Zerbib, Marc; Mahmoudi, Abdel; Latorzeff, Igor
Abstract This French observational, longitudinal, prospective study described the health-related quality of life (HRQoL) of elderly men (≥75 years old) with prostate cancer after initiating gonadotropin-releasing hormone (GnRH) agonist therapy. At baseline and 3–6 months after baseline, European Organisation for Research and Treatment of Cancer quality of life questionnaire-core 30 (QLQ-C30) and prostate-specific (QLQ-PR25) questionnaires were completed by patients. Data from 1276 patients were analyzed. At baseline, mean (±SD) age was 80 (±4.1) years, 29.1% of patients had Gleason scores ≥8 and 24.9% had metastases. At baseline, increasing age, presence of metastasis and presence of comorbidity had a negative impact on QLQ-C30 and QLQ-PR25 scores. At follow-up, improvement in emotional-functioning (2.8; p < 0.001), social-functioning (1.7; p = 0.011), global HRQoL (1.6; p = 0.029), sleep-disturbance (−2.1; p = 0.011), appetite-loss (−4.0; p < 0.001) and pain (−4.1; p < 0.001) QLQ-C30 scores were observed. In addition, there was a worsening in treatment-related symptom (8.6; p < 0.001), sexual-activity (−5.5; p < 0.001) and sexual-functioning (−22.6; p < 0.001) QLQ-PR25 scores, and an improvement in urinary symptoms (−3.7; p < 0.001) and incontinence aid (−2.9; p = 0.023) QLQ-PR25 scores. This study shows that, apart from the expected impact on sexual functioning domains, HRQoL is not adversely affected by 3–6 months of GnRH agonist therapy in older men with prostate cancer.